(3TQM HOjYjI Uaj GdOjf GdMdjs - (3YHO GdYRjR Hf SQGjG Hf Ydj Hf CHj GdbGSe GdSfHSj GdWGFj GdMdj , Uaj GdOjf,J (B750 (3g` s
(3ChdgG (B:s
(3hef CVGa ef gPg GdeMGSf Ch ZjQgG TjFkG Edi GdHOjY ef ZjQ QCjfG adg CNJjGQg hcGf LYdg eG LeY efgG SHYg YTQ fhYkG s
(3BNQgG (B:s
(3gh BNQ eG Ufa ai YUQi hCcKQ ef gPg GdcJH ehLhOg YfOi , JNJda YfOi ZjQgG de CNWQ Edi eWGdYJg dbdI CTJgGQg s
(3GdfSNI HgG MhGTs
(3JfbU ef ChdgG ebOGQ UaMgs
(3JJab ai CNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGXs
(3fSNI KGfjg s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs